“Eroding Social Capital through incompatible Legal and Institutional Regime: Experiences from Irrigation Systems in Nepal” by Dr. Prachanda Pradhan - Pradhan, Ujjwal (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
Farmer Managed Irrigation System Promotion Trust, Kathmandu, Nepal: 1st Edition 2010; 89 pp.; NRs 200 DOI: http://dx.doi.org/10.3126/hn.v8i0.4931 Hydro Nepal: Journal of Water, Energy and Environment Issue No. 8, 2011 January Page: 72-74 Uploaded date: 23 June, 2011